1976
DOI: 10.4269/ajtmh.1976.25.891
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of North American Mammals with Epidemic Venezuelan Encephalitis Virus

Abstract: Eighty-three wild mammals of ten species were inoculated with a first mouse passage level Venezuelan encephalitis (VE) virus isolated from south Texas in 1971 during the VE outbreak. Rodents were highly susceptible to VE infection and circulated VE virus at levels ranging from 10(7.7) to 10(11.5) suckling mouse intracranial lethal doses per ml for 2 to 4 days. These levels of virus could easily infect vector mosquitoes. Mortality was high in all species of rodents except Sigmodon hispidus, adult Neotoma microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In that study, mammals of 10 genera had VEEV-specifi c antibodies. In 2 follow-up studies in which wild mammals and wild birds were infected with a strain of VEEV-IB isolated during the outbreak, viremia and mortality rates for rodents were high (21,22). In a longitudinal fi eld study performed concurrent with the study reported here, seroprevalance for wild rodents was found to be much lower than previously found for this area (11).…”
Section: Discussion Reservoir Status and Potentialmentioning
confidence: 41%
“…In that study, mammals of 10 genera had VEEV-specifi c antibodies. In 2 follow-up studies in which wild mammals and wild birds were infected with a strain of VEEV-IB isolated during the outbreak, viremia and mortality rates for rodents were high (21,22). In a longitudinal fi eld study performed concurrent with the study reported here, seroprevalance for wild rodents was found to be much lower than previously found for this area (11).…”
Section: Discussion Reservoir Status and Potentialmentioning
confidence: 41%
“…In our previous study [26] we demonstrated that V3000 virus, rescued from a cDNA of VEEV [8], can be completely inactivated with INA in vitro. In this study we tested the safety and protective efficacy of INA-inactivated V3000 in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Virus: Molecularly cloned virulent strain of VEEV, V3000 [8] and an attenuated strain, V3526 [34] were used in the present study.…”
Section: Virus and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Laboratory studies have shown that a variety of wild rodents from several different genera survive experimental infection, develop high viremia, and strong antibody responses after infection with various VEEV strains. [17][18][19][20] Understanding which vertebrate species serve as the primary amplifying/reservoir hosts can help to elucidate the natural transmission cycle and may inform how arboviruses can emerge from enzootic precursors to cause human and animal disease. Determining the roles of mosquitoes as enzootic and/ or epizootic vectors is also needed to anticipate and respond to epizootic VEEV emergence.…”
Section: Introductionmentioning
confidence: 99%